Integrated multi-omics and bioinformatic methods to reveal the mechanisms of sinomenine against diabetic nephropathy - Yan Li; Lei Wang; Jimin Zhang; Bojun Xu; Huakui Zhan (BMC Complementary Medicine and Therapies, 2023)
Abstract Objectives Diabetic Nephropathy (DN) is a serious complication of diabetes, the diagnosis and treatment of DN is still limited. Sinomenine (SIN) is an active extract of herbal medicine and has been applied into the therapy of DN. Methods In the part of bioinformatic analyses, network pharmacology and molecular docking analyses were conducted to predict the important pathway of SIN treatment for DN. In-vivo study, DN rats were randomized to be treated with vehicle or SIN (20 mg/kg or 40 mg/kg) daily by gavage for 8 weeks. Then, the pharmacological effect of SIN on DN and the potential mechanisms were also evaluated by 24 h albuminuria, histopathological examination, transcriptomics, and metabolomics. Results Firstly, network pharmacology and molecular docking were performed to show that SIN might improve DN via AGEs/RAGE, IL-17, JAK, TNF pathways. Urine biochemical parameters showed that SIN treatment could significantly reduce 24 h albuminuria of DN rats. Transcriptomics analysis found SIN could affect DN progression via inflammation and EMT pathways. Metabolic pathway analysis found SIN would mainly involve in arginine biosynthesis, linoleic acid metabolism, arachidonic acid metabolism, and glycerophospholipid metabolism to affect DN development. Conclusions We confirmed that SIN could inhibit the progression of DN via affecting multiple genes and metabolites related pathways.